Review—A Portable Voltammetric Sensor for Determining Titratable Acidity in Foods and Beverages. Issue 3 (1st January 2020) - Kotani, Akira; Kusu, Fumiyo; Takamura, Kiyoko; Hakamata, Hideki
Abstract : When 3, 5-di- t -butyl-1, 2-benzoquinone (DBBQ) is electrochemically reduced in an unbuffered solution, the addition of small amounts of acid to the solution is found to give rise to a new peak (termed the prepeak) at a more positive potential than the original reduction potential of DBBQ. In addition, the prepeak current heights of DBBQ are proportional to the added acid concentration. From these findings, we utilized the voltammetric behaviors of DBBQ to develop an analytical method for the determination of titratable acidity in food and beverage samples. Moreover, a portable voltammetric sensor (weight, 100 g; power, two AAA batteries), that implements this analytical method, was developed in order to provide an on-site analytical device. To show the applicability of this portable sensor, the determination of titratable acidity in fruit juice, wine, Japanese sake, and shochu was performed. The results obtained by the portable sensor showed a good correlation with those from official potentiometric titration using 0.1 mol/L NaOH. In conclusion, the present sensor required a reduced sample volume and measurement time for an assay compared with conventional potentiometric titration, consequently showing potential for quality assessment in a wide range of food and beverage analyses.